Penerapan Framework CI (Codeigniter) pada Pemesanan Wedding Organizer (Studi Kasus CV. Nugie Wedding Organizer Besuki) - Syafiih, M .; Nadiyah, Nadiyah; Muafi, Muafi (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2023)
Nugie Wedding Organizer is a service that helps prepare and organize wedding events. For those who are inexperienced and do not have enough time and energy to prepare for a wedding, this service provides facilities to carry out and launch all desired wedding activities. The process of ordering customers for Nugie Wedding Organizer services is still done manually where customers have to come to the office directly to place orders and pay for packages, so it takes a lot of time. And the customer data recording system is also done manually, namely by recording in the book. To facilitate the work of the owner of the Nugie Wedding Organizer, there needs to be an update which changes the old system with the new system. The goal is to make it easier for customers to make the process of ordering wedding packages online through a new system that was created and make it easier for Nugie Wedding Organizer owners to serve orders and process customer data. This new system utilizes the codeigniter framework in making programs to be more organized and focused on the functionality needed when building this wedding organizer booking application. The research method used is the Rapid Application Development (RAD) method which goes through several stages. The results of research conducted using internal and external tests obtained a value of 81.67% which can be concluded that this new system is approved for use.